Hak-Hak Ekonomi Perempuan Dalam Islam - Pohan, Miranda Nasati; Siregar, Revita Mala (PT Anugerah Literasi Indomedia, 2025)
Islam provides clear recognition of women's economic rights, including the right to dowry and alimony, the right to inheritance, the right to property ownership, and the right to manage property. In addition, Islam also guarantees women's rights in the fields of education, social and political participation, the search for knowledge, and contribution to people's lives. However, in practice, there are still various forms of gender inequality, especially in women's economic participation in the Muslim world, which are largely influenced by patriarchal biased interpretations of religion. This research aims to examine the concept of women's economic rights in Islam as well as efforts to reinterpret religious texts carried out by progressive scholars in order to realize gender justice. This study uses a literature research method with a normative-theological qualitative approach through analysis of the Qur'an, hadith, jurisprudence, and relevant scientific literature. The results of the study show that Islam has basically laid a normative foundation for the realization of justice and equality between men and women, including in the economic field. The reinterpretation of religious texts opens up a wider space for Muslim women to access the right to work, earn income, and actively participate in economic activities. One of the strategies that is considered relevant in increasing the economic participation of Muslim women is the strengthening of entrepreneurship, because it allows women to play a role in the public sphere without neglecting responsibilities in the domestic sphere. Thus, women's economic empowerment through entrepreneurship can be understood as a form of actualization of Islamic justice values in the contemporary social context. Islam memberikan pengakuan yang jelas terhadap hak-hak ekonomi perempuan, antara lain hak memperoleh mahar dan nafkah, hak dalam kewarisan, hak kepemilikan harta, serta hak mengelola properti. Selain itu, Islam juga menjamin hak-hak perempuan dalam bidang pendidikan, partisipasi sosial dan politik, pencarian ilmu pengetahuan, serta kontribusi dalam kehidupan masyarakat. Meskipun demikian, dalam praktiknya masih ditemukan berbagai bentuk ketimpangan gender, khususnya dalam partisipasi ekonomi perempuan di dunia Muslim, yang sebagian besar dipengaruhi oleh penafsiran keagamaan yang bias patriarki. Penelitian ini bertujuan untuk mengkaji konsep hak-hak ekonomi perempuan dalam Islam serta upaya penafsiran ulang terhadap teks-teks keagamaan yang dilakukan oleh para ulama progresif dalam rangka mewujudkan keadilan gender. Penelitian ini menggunakan metode penelitian kepustakaan dengan pendekatan kualitatif normatif-teologis melalui analisis terhadap Al-Qur’an, hadis, kitab fikih, serta literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa Islam pada dasarnya telah meletakkan landasan normatif bagi terwujudnya keadilan dan kesetaraan antara laki-laki dan perempuan, termasuk dalam bidang ekonomi. Penafsiran ulang terhadap teks-teks keagamaan membuka ruang yang lebih luas bagi perempuan Muslimah untuk mengakses hak bekerja, memperoleh pendapatan, dan berpartisipasi aktif dalam kegiatan ekonomi. Salah satu strategi yang dinilai relevan dalam meningkatkan partisipasi ekonomi perempuan Muslimah adalah penguatan wirausaha, karena memungkinkan perempuan berperan di ranah publik tanpa mengabaikan tanggung jawab di ranah domestik. Dengan demikian, pemberdayaan ekonomi perempuan melalui wirausaha dapat dipahami sebagai bentuk aktualisasi nilai-nilai keadilan Islam dalam konteks sosial kontemporer.